HER-2/NEU overexpression in vulvar Paget disease: the Yale experience. Issue 6 (23rd April 2010) - Richter, Christine E; Hui, Pei; Buza, Natalia; Silasi, Dan-Arin; Azodi, Masoud; Santin, Alessandro D; Schwartz, Peter E; Rutherford, Thomas J
Abstract : Aims: To determine the level of HER-2/neu overexpression in vulvar Paget disease (PD) in order to assess the possibility of using HER-2/neu as a target for the treatment of Paget disease. Methods: A medical record search identified 39 patients with a histologically confirmed diagnosis of vulvar PD between 1986 and 2009. A tissue microarray containing all 39 tumour samples was created, and corresponding sections were stained immunohistochemically with an anti-HER-2/neu-antibody (HercepTest). Staining results were reported on a scale from 0 to 3+. 2+ and 3+ were considered as HER-2/neu overexpression. The HER-2/neu expression was correlated with clinical, pathological and outcome data. Results: Negative staining for HER-2/neu was noticed in four patients (12%), 1+ in 10 patients (30%), 2+ in 11 patients (33%) and 3+ in eight patients (25%), resulting in 19 patients with HER-2/neu overexpression (2+ and 3+, 58%) and 14 patients without HER-2/neu overexpression (0 and 1+, 42%). The proportion of HER-2/neu overexpression was higher in the patients with invasive than with non-invasive PD (71%, n=5/7 invasive PD vs 54%, n=14/26 non-invasive PD). There was no significant correlation between HER-2/neu staining results and clinical, pathological or outcome data. Conclusions: Surgical treatment of vulvar Paget disease is associated with a high recurrence rate and extensive reconstructive procedures. In this study, over 50% of the patients with vulvar Paget disease overexpress HER-2/neu. Anti-HER-2/neu-antibodies like trastuzumab may therefore be an interesting treatment option for HER-2/neu-positive vulvar Paget disease. Clinical trials are needed to evaluate the efficacy of trastuzumab in this disease.